Development of a Direct Aggression and Restriction Observation Checklist (AROC) for Routine Observation in Residential and Inpatient Services for Adults with Intellectual Disabilities. Issue 1 (3rd April 2019) - Nagy, Ede; Wehmeyer, Meike; Gaese, Franziska; Nicolai, Elisabeth; Schweitzer-Rothers, Jochen
ABSTRACT: Introduction : This article describes the development of an Aggression and Restriction Observation Checklist (AROC) for use in residential and in-patient services for adults with intellectual disabilities (ID). The AROC was developed in collaboration between researchers and frontline staff. It assesses self-, person-, and object-directed aggressive behaviours and the staff's use of restrictive measures, as well as mechanical restraints, physical restraints, or exclusions requested by the residents/patients themselves. AROC has been developed as an outcome tool to measure changes in the level of incidents during a two-year collaboration with professional carers (both residential and ward staff) participating in a family-systems staff training SYMPA-ID. Psychometric properties of the checklist and program´s effects on the incidents were examined. Methods : Inter-coder agreements were analysed using Kendall's coefficient of concordance. Test-retest reliability was tested by the intraclass correlation coefficient. Trends of incidents on the psychiatric ward were analysed by descriptive statistics, changes in group homes over time by linear multilevel mixed-effects models. Results : AROC demonstrates a high interrater and test-retest reliability and is easy-to-use by frontline staff working shifts. Mixed-effects models showed that aggressive behaviour was associated with both autism spectrum disorder and severity of ID. This corresponds with previous findings and indicates a convergent validity of the checklist. No effect of time was found, so that the efficacy of the intervention on the number of incidents could not be shown. Conclusions : AROC provides a low-threshold method for measuring aggression and restrictions in the daily routine of residential care homes and in-patient services as well as in scientific studies. The study provides support for the reliability and validity of the AROC.